CircZFR involves propofol-triggered ferroptosis in lung cancer cells through the IGF2BP2/GPX4 axis - Yu, Xiaocui; Gu, Yuhui; Wang, Shao; Yin, Chunyang; Liao, Xin; Liao, Xucai (Journal of investigative medicine, 2025)
This study aims to delineate the underlying mechanism by which propofol triggers ferroptosis in lung cancer cells through the inhibition of the circZFR/IGF2BP2/GPX4 axis. The expression levels of circZFR, insulin-like growth factor 2 binding protein 2 (IGF2BP2), and glutathione peroxidase 4 (GPX4) in lung cancer cells were assessed using quantitative real-time polymerase chain reaction and Western blot analysis. Cell viability was evaluated with the cell counting kit-8 assay, and ferroptosis-related indicators were measured using appropriate kits. The interactions between circZFR and IGF2BP2, as well as between GPX4 and IGF2BP2, were investigated through RNA pull-down and RNA immunoprecipitation assays, and their effects on ferroptosis were analyzed using rescue assays. In addition, xenograft assays in nude mice were conducted to evaluate the impact of propofol on tumor growth and ferroptosis in vivo. Propofol treatment induced cell ferroptosis, as evidenced by decreased cell viability and elevated levels of malondialdehyde (MDA), Fe , and lipid reactive oxygen species in H1299 and SPC-A-1 cells. In addition, propofol reduced the expression of circZFR and GPX4 in lung cancer cells. Notably, the overexpression of circZFR inhibited propofol-induced ferroptosis in these cells. CircZFR interacts with IGF2BP2 to regulate the stability of GPX4 mRNA and its protein expression. Furthermore, circZFR inhibited GPX4-mediated ferroptosis by enhancing IGF2BP2 expression in both H1299 and SPC-A-1 cell lines. Moreover, propofol inhibited tumor growth in nude mice, downregulated the expression of circZFR, IGF2BP2, and GPX4, and increased MDA and Fe levels in tumor tissues. Propofol downregulates circZFR to inhibit the expression of GPX4 by interacting with IGF2BP2, thereby triggering ferroptosis in lung cancer cells.